Respuesta :
Answer:
Step-by-step explanation:
Given 3x - 2y = 0, which can be re-written as 3x = 2y, find the intercepts.
y-intercept: let x = 0 and find y. y = 0. So the y-intercept is (0, 0).
x-intercept: let y = 0 and find x. The x-intercept is (0, 0) also.
Answer:
Step-by-step explanation:
Given 3x - 2y = 0, which can be re-written as 3x = 2y, find the intercepts.
y-intercept: let x = 0 and find y. y = 0. So the y-intercept is (0, 0).
x-intercept: let y = 0 and find x. The x-intercept is (0, 0) also.
Read more on Brainly.com - https://brainly.com/question/12681291#readmore